2005
DOI: 10.1007/s11373-005-9030-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced nuclear factor-kappa B-associated Wnt-1 expression in hepatitis B- and C-related hepatocarcinogenesis: identification by functional proteomics

Abstract: SummaryChronic infections with hepatitis B and C viruses (HBV and HCV) are etiologically linked to hepatitis, liver cirrhosis, and hepatocellular carcinoma (HCC). Both viruses may induce activation of nuclear factor-kappa B (NF-jB) in hepatocytes that plays a crucial role in the regulation of cell growth and apoptosis. Functional proteomics analysis of proteins associated with NF-jB signaling complexes in both viruses-related HCC tumor and non-tumor tissues may disclose possible common mechanisms in hepatocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 69 publications
(93 reference statements)
1
24
0
Order By: Relevance
“…It shows that the Wnt-1-mediated survival of PC12 cells is dependent on NF-jB activation, and that stable expression of Wnt-1 increases NF-jB activity [19]. This link can be indirectly supported in our recent report that functional proteomics identifies enhanced expression of NF-jBassociated Wnt-1 protein in human hepatocellular carcinoma (HCC) tissues [20]. However, a direct evidence of NF-jB activation relating to the production of Wnt-1 protein in human cells remains elusive.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…It shows that the Wnt-1-mediated survival of PC12 cells is dependent on NF-jB activation, and that stable expression of Wnt-1 increases NF-jB activity [19]. This link can be indirectly supported in our recent report that functional proteomics identifies enhanced expression of NF-jBassociated Wnt-1 protein in human hepatocellular carcinoma (HCC) tissues [20]. However, a direct evidence of NF-jB activation relating to the production of Wnt-1 protein in human cells remains elusive.…”
mentioning
confidence: 76%
“…Inc., South San Francisco, CA , USA) was performed by the procedures described previously [20]. The quantity of Wnt-1 protein production was semi-quantitatively estimated on the immunoblot films with ImageMaster TotalLab, Version 2.01 (Amersham Parmacia Biotech, NJ, USA), and data were estimated and expressed as relative density to HepG2 cell control.…”
Section: Assessment Of Anti-sense Morpholino Ons-induced Apoptosismentioning
confidence: 99%
“…Western blotting of tumor and nontumor proteins with biotin-conjugated rabbit anti-human WNT1 polyclonal antibody (Zymed Laboratories, Inc.) was conducted by the procedures described previously (18). The amount of Wnt-1 protein was semiquantitatively measured on the immunoblot films with ImageMaster TotalLab version 2.01 (Amersham Parmacia Biotech), and all data were expressed as tumor/ nontumor ratio.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14][15][16]. Functional proteomics and cDNA microarray studies have shown up-regulation of Wnt-1 in HBV-and HCVrelated HCC tissues and cell lines (17)(18)(19). Wnt-1 protein processing and secretion have been extensively characterized for the 36-kDa unglycosylated form as well as sequentially glycosylated forms of 38-, 40-, and 42-kDa forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation